THEORY OF COORDINATION AND REGULATION OF MOVEMENTS AND ITS INVESTIGATIVE AND FORENSIC APPLICATIONS - V. Tolstolutsky; V. Pronin (Теория и практика судебной экспертизы, 2015)
The authors argue for a need to develop forensic methodologies based on Nikolai Bernstein's theory of coordination and regulation of movements, as an aid in addressing the diagnostic and identi"cation objectives of forensic investigation.